Organ transplants of the future: planning for innovations including xenotransplantation. (6th October 2021) - Cozzi, Emanuele; Schneeberger, Stefan; Bellini, Maria Irene; Berglund, Erik; Böhmig, Georg; Fowler, Kevin; Hoogduijn, Martin; Jochmans, Ina; Marckmann, Georg; Marson, Lorna; Neuberger, James; Oberbauer, Rainer; et al.
Summary: The future clinical application of animal‐to‐human transplantation (xenotransplantation) is of importance to society as a whole. Favourable preclinical data relevant to cell, tissue and solid organ xenotransplants have been obtained from many animal models utilizing genetic engineering and protocols of pathogen‐free husbandry. Findings have reached a tipping point, and xenotransplantation of solid organs is approaching clinical evaluation, the process of which now requires close deliberation. Such discussions include considering when there is sufficient evidence from preclinical animal studies to start first‐in‐human xenotransplantation trials. The present article is based on evidence and opinions formulated by members of the European Society for Organ Transplantation who are involved in the Transplantation Learning Journey project. The article includes a brief overview of preclinical concepts and biology of solid organ xenotransplantation, discusses the selection of candidates for first‐in‐human studies and considers requirements for study design and conduct. In addition, the paper emphasizes the need for a regulatory framework for xenotransplantation of solid organs and the essential requirement for input from public and patient stakeholders.